Pengaruh Bauran Pemasaran (Marketing Mix) Terhadap Keputusan Pembelian Konsumen Buah Stroberi (Fragaria X Ananassa), Di Lumbung Stroberi, Desa Pandanrejo, Kecamatan Bumiaji, Kota Batu - Landu Tana, Albertus; Triwulan Budisaptorini, Anasthasia; Puri Nurani, Maria (BiSTeK Pertanian, 2023)
Strawberries are a hybrid plant species of the genus Fragaria. This plant is a popular plant that is often well cultivated throughout the world. Fruits have special characteristics, especially in shape, color, texture, taste and aroma. The purpose of this study was to determine the effect of the marketing mix on purchasing decisions for strawberries and to determine the dominant marketing mix influencing purchasing decisions for strawberries in Pandanrejo Village, Bumiaji District, Batu City. The research location is in the Strawberry Barn, Pandanrejo Village, Bumiaji District, Batu City. Determination of the sample in this study using accidental sampling with the Slovin formula, the sample in this study amounted to 60 respondents. The purpose of this study was to determine the effect of the marketing mix on purchasing decisions of strawberries and to determine the dominant marketing mix influencing purchasing decisions of strawberries The results of this study indicate that the independent variable of the marketing mix (X) has a significant effect on the dependent variable on the purchasing decision of strawberries (Y). Product variables (X1), price (X2), promotion (X3), and place (X4) have a partial effect on purchasing decisions for strawberries (Y). The dominant variable influencing the decision to buy strawberries is the place variable (X4). This is because the beta coefficient value of the place variable is greater than the product beta coefficient (X1), price (X2), and promotion (X3)